Test Logistics Maturity of the Industrial Zone in the Region of Gabes - Olfa Jellouli; Manel Abdelkadhi (International Journal of Supply Chain Management, 2013)
Faced with globalization, companies are faced with the challenge of achieving the logistics maturity. This is the purpose of this article is the result of a survey conducted in the region of Gabes in Tunisia. For the understanding of the questionnaire developed some elements regarding logistical audit techniques to improve productivity and integrated logistics and cooperated. The most important in this article is the content of training that will allow the cited becoming a logistics hub in mature area.